(untitled) (CIPEEX, 2022)
OLDER PEOPLE ARE OFTEN STEREOTYPED AS NON-SEXUAL BEINGS. IN PLACE OF THE IDEA OF SENIORS LOSINGINTEREST IN SEX, THE SOCIETY NEEDS TO UNDERSTAND THEIR OWNVALUES AND ATTITUDES REGARDING THIS THEME. ACTUALLY, SEXUALITY IS A WELL-KNOWN TOPIC, BUT IT SEEMS TO BE TREATEDLITTLE WHEN IT CONCERNS THE ELDERLY. THUS, THE CURRENTINTEGRATIVE MANUSCRIPT ESSAY AIMED TO OBSERVE THERELATIONSHIP BETWEEN ASPECTS OF SEXUALITY AND THE ELDERLYQUALITY OF LIFE. THE DATA SEARCH WAS GUIDED BY THE PICO TOOL AND CARRIED OUT ON THE SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND SCIENCEDIRECT PLATFORMS. THIS STUDYWAS INSPIRED BY 17 ORIGINAL MANUSCRIPT ARTICLES, USINGHEALTH DESCRIPTORS, PUBLISHED FROM 2016 TO 2022. ACCORDING TO THE ARTICLES ANALYZED, THE RESULTS HIGHLIGHTTHE ELDERLY QUALITY OF LIFE WAS POSITIVELY CORRELATED WITHSEXUALITY, WHICH ENCOMPASSES CULTURAL, PSYCHOLOGICAL, AND PHYSICAL FACTORS, ABLE OF ENHANCING AND/OR MITIGATINGTHEIR RESPECTIVE SEXUAL EXPERIENCES. TO CONCLUDE, THERE ISA NEED TO RESEARCH OLDER PEOPLE MORE OFTEN. FURTHERMORE, TO EXPAND THE ANALYSIS ON THE RELATIONSHIP BETWEEN THEDIMENSIONS OF QUALITY OF LIFE AND SEXUALITY.